2023
DOI: 10.1177/17534666231158283
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in patients with stable COPD in China: analysis of a prospective, 52-week, nationwide, observational cohort study (REAL)

Abstract: Background: Underdiagnosis and undertreatment pose major barriers to optimal management of chronic obstructive pulmonary disease (COPD) in China. Objective: The REAL trial was performed to generate reliable information on real-world COPD management, outcomes and risk factors among Chinese patients. Here, we present study outcomes related to COPD management. Design: It is a 52-week, prospective, observational, multicentre study. Methods: Outpatients (aged ⩾40 years) enrolled from 50 secondary and tertiary hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Given the potential impact of residence area (rural versus urban) on disease burden, this may also partly explain the difference in exacerbation rates observed across geographic regions in China. In the REAL study, the northwest region had the highest proportion of rural residents (64.6%) 14 and also the highest rate of exacerbation that resulted in hospitalisation, while the north and east were among regions with the highest proportion of urban residents (59.9–62.0%) 14 and with the lowest rate of exacerbation that resulted in hospitalisation. The lack of high-level medical institutions in rural areas may limit access to specialist medical services and optimal COPD management.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Given the potential impact of residence area (rural versus urban) on disease burden, this may also partly explain the difference in exacerbation rates observed across geographic regions in China. In the REAL study, the northwest region had the highest proportion of rural residents (64.6%) 14 and also the highest rate of exacerbation that resulted in hospitalisation, while the north and east were among regions with the highest proportion of urban residents (59.9–62.0%) 14 and with the lowest rate of exacerbation that resulted in hospitalisation. The lack of high-level medical institutions in rural areas may limit access to specialist medical services and optimal COPD management.…”
Section: Discussionmentioning
confidence: 97%
“…requiring hospitalisation) as the severity of COPD increased. 20 We have previously reported that secondary hospitals had a greater proportion of patients with very severe COPD compared with tertiary hospitals, 14 which may have contributed to the differences in exacerbation rates across hospital tiers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations